Analisis potensi ekonomi dan kependudukan Kabupaten Ogan Komering Ilir - Andikaputra, Andre (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The government must be able to maximize the economic potential of the region. it can be accomplished through understanding the sectors that support economic growth. Population conditions also have a relationship with economic growth. The government of Ogan Komering Ilir has to understand the basic sector that will encourage an increase in the GRDP of the region so that it can support the economy of the region. The purpose of this research is the analysis of the potential sector and population should be a guide for planning and development, especially economic growth in Ogan Komering Ilir. The results showed that only the agricultural, forestry and fisheries sectors was the only basic sector in Ogan Komering Ilir. Furthermore, the population growth rate for the 2015-2019 period was 1.32% which was not too high in Ogan Komering Ilir Regency. Also, the population that is the burden of the productive population looks stagnant.